The performance of Viking identity in museums - Whitehead, Gudrun D., author. Link
1 online resource (x, 247 pages)
Keywords: "The Performance of Viking Identity in Museums explores the representations and uses of Vikings in museums across Iceland, England and Norway. Drawing on theories from history, philosophy, museology, and sociology, the book analyses how the Viking myth is used by visitors to make sense of present-day society, culture, and politics and the role of museums in this meaning-making process. Demonstrating that the Viking myth is present in collective memory and plays an important role in the construction and modification of collective, national, and personal identities, the book analyses this process through the framework of museums and their visitors. Identifying museums as places where heritage, identity and social norms are affirmed and reflected upon, Whitehead demonstrates that all countries use their Viking heritage to define their identity on a local and international level--through tourist attractions such as museums and other Viking-related monuments and merchandise. Providing readers with an insight into Vikings and their social relevance today, The Performance of Viking Identity in Museums will be of great interest to academics and researchers across the social and human sciences. It should also be essential reading for museum professionals working in museums around the world."--